LITERATUR REVIEW: MENINGKATKAN KEMAMPUAN MENULIS MELALUI PEMANFAATAN MAJALAH DINDING PADA SISWA DI SEKOLAH DASAR - Wawan Setiyawan; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Writing ability is a crucial component of literacy education at the elementary level, yet it remains one of the most persistent challenges for Indonesian students. This article aims to review and synthesize empirical findings from various studies examining the utilization of wall magazines (mading) as an instructional medium to enhance students’ writing proficiency. Employing a systematic literature review design, this study analyzed scholarly works published between 2015 and 2025 from databases such as Google Scholar, ResearchGate, and PubMed. The data were processed through reduction, organization, and synthesis techniques to reveal recurring patterns and key themes. Results indicate that wall magazines serve not only as a platform for creative expression but also as an effective pedagogical tool that fosters writing competence, motivation, and collaborative learning among students. Additionally, wall magazines contribute to cultivating a school-wide literacy culture by providing an authentic and participatory learning environment. The review concludes that mading represents an innovative and contextually relevant approach to improving writing skills in elementary education. Future research is encouraged to integrate digital wall magazines (e-wall magazine) and mixed-method triangulation to explore more comprehensively how literacy media influence students’ writing development in the digital era.